Method and arrangement for adaptive switching off of the exhaust brake in connection with upshift - ANDERSSON; ROGER (1996)
The invention relates to an improved method and an arrangement for implementation of that method for obtaining safer and quicker upshifts while maintaining gear change comfort, using computer-assisted systems for gear change in mechanical gearboxes in motor vehicles, preferably without clutch disengagement between engine and gearbox. In connection with upshift, an exhaust brake is activated, (EBon) at time t1 in parallel with the fuel (FUEL) to the engine being reduced to zero quantity. The engine speed n2 is thereby reduced more quickly to the speed n1 which is the synchronous engine speed for the next higher gear. The speed reduction is monitored with a view to achieving rapid engine speed bracketing to synchronous speed, and also good gear change smoothness and safe gear engagement. The exhaust brake switch-off point EBoff at time t2 is adjusted adaptively for subsequent upshift by a connection factor EBAoff so that the engine speed falls to a level Maxdip within a predetermined speed range below the synchronous engine speed, preferably between 15 and 50 rpm below the synchronous speed.